Exploring the Traffic Congestion and Improving Travel Time Reliability Measures in Heterogeneous Traffic Environments: A Focus on Developing Countries - Ranjan Samal, Satya; Mohanty, Malaya; Gorzelanczyk, Piotr (Communications - Scientific Letters of the University of Zilina, 2023)
Traffic congestion is a pervasive issue that affects urban areas worldwide. This study investigates congestion on urban roads in an Indian smart city. Video graphic technique was employed to collect data across various traffic volumes. Travel time for different vehicle categories was estimated, and the travel time reliability congestion index was assessed. Multiple linear regression modelling was utilized to assess the attributes influencing congestion. Traffic signal synchronization and enforcement of traffic regulations, decentralization of important offices, and regulating roadside activities received strong recommendations from the majority of inhabitants. For improving the functionality and accessibility, related to the urban road network, these attributes should be enforced. The research intended to assess the functional effectiveness of urban roads using travel time reliability measures.
Keywords: traffic congestion; travel time; congestion index; reliability measures; linear regression